1989
DOI: 10.1111/j.1365-2141.1989.tb06272.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic differentiation of chronic B‐cell malignancies using monoclonal antibody L161 (CD1c)

Abstract: The expression of membrane CD1c, as defined by monoclonal antibody L161, was examined on malignant lymphoid cells from 191 cases of chronic lymphoproliferative disease and on eight 'normal' enriched tonsil B-cell extracts. Of 79 cases of chronic lymphocytic leukaemia (CLL) studied, 77 showed low (less than 20% positive cells) CD1c expression whereas 63/71 (89%) cases of B-PLL, HCL and B-NHL showed increased CD1c+ (but not CD1a or CD1b) components. In contrast, malignancies corresponding to terminal stages of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…we investigated the expression of this determinant on leukaemic B eells. and reported maximal expression on B-NHL cells [22]. This was independently confirmed by a separate study, which identified a eorrelation between immunophenotypically defined difTerentiation stage and anatomical location in B-cell subpopulations [26].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…we investigated the expression of this determinant on leukaemic B eells. and reported maximal expression on B-NHL cells [22]. This was independently confirmed by a separate study, which identified a eorrelation between immunophenotypically defined difTerentiation stage and anatomical location in B-cell subpopulations [26].…”
Section: Discussionmentioning
confidence: 68%
“…Further potential candidates for the tnantle of Qa-like antigens arc the HLA-linked TCA [19] and HT [20,21] moiccuics. Having previously reported the expression of CD I c on malignant B cells at defined stages of differentiation [22]. this study was undertaken to quantify the level of CDlc expression and lo further explore the possibility that additional /iim-associated non-HLA class I molecules arc expressed on leukaemic B cells.…”
mentioning
confidence: 99%
“…The immunological phenotypes ofJOK-1 and Daudi, compared with those of HC phenotyped in our and other laboratories (15,16,17,18,19,20,21,22), are shown in Table 1. Whereas the surface antigens on Daudi and JOK-1 were very similar, except that Daudi is MHC class I-negative, several differences were observed between the cell lines and HC.…”
Section: Surface Antigen Profile Of Daudi and Jok-1mentioning
confidence: 95%
“…SLVL: (a) moderate-to-large sized cells with unevenly distributed, short cytoplasmic projections -(b) intense CD lc staining of the cell membrane and projection (peripheral blood -x800). LPC NHL: (c) 2 large-sized plasmacytoid cells with basophilic cytoplasm -(d) cytoplasmic positivity CD25 (peripheral blood -x800).invariably low expression of CDlc by B-CLL cells, were recently obtained by Jones et al(18) who studied a large number of cases diagnosed on the basis of well-defined morphophenotypic features. Some other minor discrepancies, however, concern the expression of CD 1 lc and CD25 on B-CLLs: Erber et al(16) and Inghirami et al(19) recently reported, respectively, 21 % and 47 % of B-CLL to be CD 1 lc-positive.…”
mentioning
confidence: 99%